Multi Phase Center Processing of Ice Sounding Radar Signals for Across Track Surface Clutter Cancellation: MPC Processing Tool User Manual - Scheiber, Rolf; Prats, Pau (2013)
ESA’s POLarimetric Airborne Radar Ice Sounder demonstrator (POLARIS) - build and operated by the Technical University of Denmark (DTU) - operates at P-band and features a multi-phase-center antenna for the purpose of surface clutter suppression. The first data suitable for the development and demonstration of suitable surface clutter cancellation methods were acquired in February 2011 during the IceGrav campaign in Antarctica. The purpose of the present study is to investigate and compare different methods for POLARIS surface clutter cancellation and to implement a Processing Tool to augment the along-track POLARIS processor developed by ESA, thus improving bedrock detectability. The present document is the User Manual for the MPC Processing Tool developed by DLR, Microwaves and Radar Institute in the frame of this contract. • Section 2 explains the software installation and how to invoke the MPC Processing Tool • Section 3 describes the Configuration File, • Section 4 explains the directory structure and Filename Convention • Section 5 lists the provided test data sets and reference processing results